Mitigating water pollution on implementation of green innovation in Kelantan - Muhammad Dzulhafiq Iqmal Md Noor; Thevaprisha Bala; Nur Amira Amelia Amran; Nurul Zahratul Husna Shaari (2024)
This research addresses the pervasive issue of Kelantan water pollution, affecting residents in Kelantan. The dissatisfaction stemming from water pollution is compounded by a need for more awareness about the potential of green innovation to mitigate this problem. Focusing on residents aged 15 to 36 years and above in Kelantan, the study employs the Theory of Planned Behaviour (TPB) and Theory of Ecological Modernization (EMT) as a theoretical framework, considering the relationship between Green Innovation, Green Environmental Awareness, Green Behavioural Intentions, and Green Product Value. The study uses quantitative research methods to distribute 400 questionnaires through convenience sampling. It employs statistical tools such as frequency analysis, descriptive analysis, reliability, normality tests, and Pearson correlation for data analysis. The findings demonstrate a high (strong) (positive) correlation between the Implementation of Green Innovation and Key Elements: Green Environmental Awareness, Behavioural Intentions, and Green Product Value. The research also provides valuable demographic insights into age, gender, race, and occupation. While acknowledging limitations related to respondent biases and data accuracy, the study recommends future research directions, emphasizing longitudinal studies, comparative analyses, and community involvement in green initiatives. The implications of this research extend to environmental policymakers, businesses, and initiatives seeking sustainable solutions to water pollution. Overall, this research significantly contributes insights into the relationship between Green Innovation, Green Environmental Awareness, Green Behavioural Intentions, and Green Product Value, paving the way for informed decision-making and practices in environmental sustainability.